Kobiecość i męskość w narracjach biograficznych młodych prekariuszy – zarys interpretacji - Drabina-Różewicz, Aleksandra (Uniwersytet Wrocławski. Wydział Nauk Społecznych. Instytut Socjologii, 2021)
The article focuses on the categories of work and gender that have been captured in biographical interviews with young precarious workers. The paper is based on an initial analysis of several interviews. The author attempts to show how the categories of work and gender shape the experiences and identities of the young workers. The paper also presents reflections on how masculinity and femininity differentiate the labor market experiences and the life strategies of young workers. The article is an attempt to show the direction of the analysis of labor and gender as the main inequalities described in the biographical narratives of young workers entering the labor market in Poland.
Keywords: femininity; masculinity; precarity; biographical research